EFFECT OF THE OCCURRENCE PROCESS OF THE PEAKS OVER THRESHOLD ON THE FLOOD ESTIMATES - Onoz B.; Bayazit M. (My University, 2001)
Partial duration (peaks over threshold) series have been used as an alternative to annual maxima series in flood frequency analysis. Poisson process is usually assumed for the occurrence of peaks. In some peaks over threshold series, variance of the annual number of exceedances is significantly smaller (or larger) than the mean. In such cases binomial (or negative binomial) distribution has a better fit. Expressions are obtained for the estimation of the T-year flood and its sampling variance when binomial (or negative binomial) model is combined with the exponential distribution of peak magnitudes. It is shown that the results are almost identical to those obtained using the Poisson model, for which much simpler expressions are available.
Keywords: FLOOD; PARTIAL DURATION SERIES; PEAKS OVER THRESHOLD; POISSON PROCESS; BINOMIAL DISTRIBUTION; NEGATIVE BINOMIAL DISTRIBUTION